Are adverse selection models of debt robust to changes in market structure? - Jukka Vauhkonen (Bank of Finland, 2003)
Many adverse selection models of standard one-period debt contracts are based on the following seemingly innocuous assumptions.First, entrepreneurs have private information about the quality of their return distributions.Second, return distributions are ordered by the monotone likelihood-ratio property.Third, financiers payoff functions are restricted to be monotonically non-decreasing in firm profits.Fourth, financial markets are competitive.We argue that debt is not an optimal contract in these models if there is only one (monopoly) financier rather than an infinite number of competitive financiers.
URN:NBN:fi:bof-20140807125
Keywords: 330